Streptococcus, Centrocestus formosanus and Myxobolus tilapiae concurrent infections in farmed Nile tilapia (Oreochromis niloticus). (September 2021) - Eissa, Alaa Eldin; Attia, Marwa M.; Elgendy, Mamdouh Y.; Ismail, Gehad A.; Sabry, Nader M.; Prince, Abdelbary; Mahmoud, Mahmoud A.; El-Demerdash, Ghada O.; Abdelsalam, Mohamed; Derwa, Hassan I.M.
Abstract: Stress triggered concurrent microbial/parasitic infections are prevalent in earthen pond based farmed Nile tilapia Oreochromis niloticus . In the current study, a total of thirty five O. niloticus were collected from a commercial fish farm with a history of severe mortalities at Port Said, Egypt. Nile tilapia samples were subjected to bacteriological, parasitological and pathological examinations. Twenty one Enterococcus fecalis and 15 Streptococcus agalactiae isolates were presumptively identified utilizing the semi-automated API 20 Strept test kit. The identities of the retrieved bacteria were confirmed by the sequencing of 16 S rRNA gene. Moribund O. niloticus were found to be heavily infected by one or both of Centrocestus formosanus encysted metacercariae ( EMC) and/or Myxobolus tilapiae spores presenting a unique form of synergistic and/or symbiotic relationship. The identities of both parasites were confirmed through morphological and molecular characterization. Variable circulatory, degenerative, necrotic and proliferative changes were also noticed in hematopoietic organs. Interestingly, multiple myxobolus spores and EMC were noticed in some histological sections. It was obvious that the current concurrent bacterial and parasitic infections are triggered by the deleterious effects of some stressing environmental conditions. The unfavorable climatic conditions (high temperature and high relative humidity) recorded at the surge of mortalities are probable predisposing stress factors. Highlights: A novel report of Streptococcus, Centrocestus and Myxobolus coinfections in Nile tilapia with linkages to erratic managemet. The pathological impacts of such concurrent infections in fish organs including the hematopoietic tissues were detailed. The incriminated parasites and bacterial pathogens were morphologically and molecularly confirmed. The linkages between poor water quality, bad weather, erratic management and eruption of these infections were discussed.